Nonclassical magnetic dynamics and negative exchange bias in Nd0.5Sr0.5MnO3 films - Prokhorov, V.G.; Pashchenko, V.P.; Svetchnikov, V.L.; Park, J.S.; Kim, J.B.; Hyun, Y.H.; Park, S.Y.; Lee, Y.P.; Komashko, V.A.; Kaminsky, G.G.; Khokhlov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The amorphous, nanoclustered, and self-organizing bilayered Nd0.5Sr0.5MnO3 films have been prepared by a rf-magnetron sputtering. The amorphous film turn out to be a typical paramagnet with a freely moving of the individual Mn spins, the magnetic properties of which are well described by the Curie–Weiss approximation. The nanoclustered film manifests the magnetic properties mimic to the superparamagnetic particles with a nonclassical magnetic dynamics. Taking into account the unique shape of the hysteresis loops, which have hysteretic lobes at high magnetic field but are nonhysteretic as the field crosses zero, we suggest that each particle (nanocluster) is the closure magnetic domain (or magnetic vortex) rather than the single one. At the same time, the blocked to unblocked transition was observed with increasing temperature similar to the usual superparamagnet. The self-organizing bilayered film demonstrates a negative exchange bias, which is typical for the ferromagnet/antiferromagnet hybrid system in spite of that both layers in our case have a ferromagnetic origin. The magnetic properties of the films are discussed in detail on the base of modern theoretical models.